Surrendering Worries to God Through a Philosophical and Theological Perspective on 1 Peter 5:7 in the Context of the Seventh-day Adventist Church - budiyanto, wahyu; Pardosi, Milton T. (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2025)
This study examines the philosophical and theological meaning of 1 Peter 5:7 within the framework of the Seventh-day Adventist Church. The study begins with the exegesis process of the text of 1 Peter 5:7, in order to understand its original meaning in the historical, linguistic, and pastoral context of the author to the Christian congregation. This verse emphasizes the importance of leaving all worries to God, a concept that is relevant in the context of an anxious life. Using theological hermeneutics and existentialistic philosophical approaches, this study explores the relationship between faith, reason, and free will in the practice of surrender to God. Ellen G. White's writings show that worry is often used by Satan to weaken faith, while surrender to God is an active act that strengthens man's spiritual relationship with Him. From a philosophical perspective, Soren Kierkegaard's thinking on the leap of faith and Stoicism regarding the acceptance of the uncontrollable also enriched the theological understanding of this verse. This study concludes that the concept of surrendering worries in 1 Peter 5:7 is not just a passive attitude, but an integration of faith and rationality that allows humans to face life's challenges with calm and complete trust in God.